The Perceptions of Yemeni Universities Students towards Practical Training and Internships in Translation Programs - Raweh, Azhar Abdulrahman; Al-Mekhlafi, Mohammad Abdu (Journal of Educational and Psychological Sciences, 2025)
An increased attention to translation and translator training programs has recently arisen. Despite the importance of translation programs globally, the quality of translation programs remains insufficient in producing effective translation professionals, especially in Yemeni universities. This study investigates the perceptions of translation students at public and private universities in Hodeidah, Yemen, regarding practical training and internships in translation programs. It aims to evaluate how the integration of practical training influences students' professional preparedness and satisfaction with their educational experiences. To achieve this objective, this study employed a closed-ended questionnaire tool for data collection, administered to 160 undergraduate translation students in their third and fourth years of study. Consequently, the collected data was analyzed using the descriptive statistical analysis program (SPSS). The findings revealed statistically significant differences in the perceptions between public and private universities students. Underscoring a critical need for curriculum improvements, particularly the integration of practical applications with theoretical concepts. The present study highlights the importance of curriculum enhancements in translation programs to better prepare students for the industry demands of practical training in translation education.This study contributes to providing a valuable insight into the development of the educational quality of translation programs in general and, particularly, in the Yemeni higher educational sector.
Keywords: Practical Training; Internships; Translator Training; Yemeni Students